Efisiensi Sistem Pelaporan Pajak sebagai Variabel Moderasi untuk Digitalisasi Kepatuhan Pajak - Indrawan, Rizki (Universitas Katolik Parahyangan, 2024)
The goal of this research is to examine the impact of tax digitalization, such as e-filling, and e-billing, on the efficiency of individual taxpayer reporting and tax compliance in the 4.0 era. The presence of tax digitalization as a type of tax administration modernization makes it easier for the general public, particularly taxpayers, to carry out their obligation. This study is a quantitative research. This study's variables include one dependent variable, two independent variables and one variabel moderating. The dependent variable is the tax compliance, while the independent variables are the use e-filling, and e-billing and the moderating variables is efficiency of taxpayer reporting. The population in this study is Individual taxpayers in Kuningan Regency, West Java. The samples in this research are 50 respondents that take the questionnaire with Likert scale as the measurement. This study used incidental sampling, with the research instrument being an online questionnaire distributed via social media. The data analysis method in this study uses Moderated Regression Analysis (MRA). According to the findings of this study efficiency tax system has not been proven to moderate the relationship between e-filling and e-billing with the tax compliance.